Gestural development of chimpanzees in the wild: the impact of interactional experience. (December 2017) - Fröhlich, Marlen; Müller, Gudrun; Zeiträg, Claudia; Wittig, Roman M.; Pika, Simone
Abstract : To understand the complexity involved in animal signalling, studies have mainly focused on repertoire size and information conveyed in vocalizations of birds and nonhuman primates. However, recent studies on gestural abilities of nonhuman primates have shown that we also need a detailed understanding of other communicative modalities and underlying cognitive skills to grasp this phenomenon in detail. Here, we thus examined gestural signalling of chimpanzees, Pan troglodytes, living in two communities in the wild (Kanyawara, Uganda; Taï South, Côte d'Ivoire) with a special focus on the influence of the social environment on signal development. Specifically, we investigated to what extent specific social factors, namely behavioural context, interaction rates and maternal proximity, affect gestural production (i.e. gesture frequency, sequences and repertoire size). We used a combination of video recordings and focal scans obtained from 11 infants aged between 9 and 69 months during 1145 h of observation throughout two consecutive field periods. Overall, we found that social play was the context in which the highest number of gestures occurred. While gesture frequency and repertoire size increased with higher interaction rates with nonmaternal conspecifics and the number of previous interaction partners, no effect was found for interaction rates with mothers. Our results thus imply that infants of social mothers may have a head start in life. Moreover, we provide hitherto undocumented evidence for sex differences in gestural signalling, which may reflect the differential importance of early socialization for chimpanzee males and females. Gestural development thus relies heavily on interactional experiences with conspecifics, which adds support for gestural acquisition via the learning mechanism of 'social negotiation' in great apes. Highlights: We examined the influence of social exposure on gestural development in chimpanzees. Social play was the major context of gestural signalling. Gestural production depended strongly upon interaction partner and experience. Gestural sex differences may mirror sex differences in sociability. Social mothers enable head starts of their infants entering the social world.